Detección molecular de Brucella sp, Leptospira spp y Toxoplasma gondii en felinos domésticos y silvestres y el impacto zoonótico en el personal encargado de su manejo en Pereira, Colombia - Caballero Méndez, Lyda C. (2023)
The study aimed to determine the presence of the infectious agents that cause toxoplasmosis, brucellosis and leptospirosis using the conventional PCR molecular technique in domestic and wild cats, as well as in the personnel related to the care and management of these animals in the city of Pereira, Risaralda. (Colombia). Blood samples were taken from domestic cats (n=99) and wild cats in captivity (n=4) and from the personnel responsible for their care and management (veterinarians, zootechnicians, and operators; n=65). A prevalence of 37% for toxoplasmosis and 1% for leptospirosis in domestic felines was estimated. The presence of these pathogens was not found in the personnel.